Analisis Tingkat Kesukaran Soal Ujian Mata Pelajaran Seni Budaya Kelas VII Di SMP Negeri 7 Padang - Rahmi, Gustia; Ardipal, Ardipal (SENDRATASIK UNP, 2021)
The purpose of this study was to determine the level of difficulty of the odd semester exam items in the arts and culture class VII SMPN 7 Padang academic year 2020/ 2021 based on the level of diffuculty. The type of research used in this research is descriptive quantitative research. The subjects in this study were all students of class VII.3 SMPN 7 Padang in the academic year 2020/ 2021. The subjects in this study were all students of class VII.3 SMPN 7 Padang in the academic year 2020/2021 with the object of research namely questions, lists of grades & remedial items for students on the mid-semester test and the answer key for the odd mid-semester test. The data were obtained by collecting data by means of documentary studies. Based on the data analysis, it was determined that the results of the analysis of the difficulty level of the odd semester examination questions for arts and culture class VII SMPN 7 Padang academic year 2020/2021 were 33 items (66%) stated in accordance with the difficulty index.